Analysis of the synergistic integration of DFMT with CAPP and MP in metal parts manufacturing based on cost analysis and systematic algorithm. (2nd March 2023) - Al-Shebeeb, Omar; Gopalakrishnan, Bhaskaran; Currie, Kenneth R.; Wuest, Thorsten; Hamrick, Todd
This research focused primarily on self-fastening characteristics, standardisation of parts and minimal use of fasteners. The work investigated the significance of synergistic design for manufacturing techniques (DFMTs), with their inherent machine element systems (MES) and machining parameters (MPs) to evaluate which DFMT has the most influence on cost reduction and increasing throughput and under which circumstances. In sum, this research applies DFMT to product design. For each DFMT and associated MES and MP, process planning was used effectively with computer aided process planning (CAPP) tools to enhance the evaluation impact of the dialogue between the design and manufacturing functions. A systematic algorithm was inherently developed and incorporated into the software tools used herein. Generative process planning software is used to measure and analyse sensitivity in plan effectiveness. The final results showed a significant improvement in cost reduction and production rates. DFMTs 1 and 2 have the main influence on the systematic algorithm. [Submitted 24 June 2020; Accepted 10 April 2021]